2018
DOI: 10.1007/s10461-018-2296-x
|View full text |Cite
|
Sign up to set email alerts
|

PrEP in the Real World: Predictors of 6-Month Retention in a Diverse Urban Cohort

Abstract: The effectiveness of HIV pre-exposure prophylaxis (PrEP) depends on adherence, which requires retention in PrEP care. We sought to examine factors associated with six-month retention in PrEP care among individuals prescribed PrEP between 2011 and 2015 in a large, academic health system in the Bronx, New York. We used multivariable logistic regression to identify factors independently associated with six-month retention. Among 107 patients, retention at six months was 42%. In the multivariable analysis, heteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 14 publications
(14 reference statements)
1
20
0
Order By: Relevance
“…13 Comparisons now need to be made to determine the rate of follow-up visits in physician-run PrEP clinics to better determine the costs of offering PrEP. Lastly, our retention rate of 50.6% (45/89) matches that in the published literature about PrEP, [22][23][24][25] and with larger reviews about medication adherence more generally, 26 with about half of persons discontinuing any oral medication after about 12 months of use.…”
Section: Discussionsupporting
confidence: 83%
“…13 Comparisons now need to be made to determine the rate of follow-up visits in physician-run PrEP clinics to better determine the costs of offering PrEP. Lastly, our retention rate of 50.6% (45/89) matches that in the published literature about PrEP, [22][23][24][25] and with larger reviews about medication adherence more generally, 26 with about half of persons discontinuing any oral medication after about 12 months of use.…”
Section: Discussionsupporting
confidence: 83%
“…The most common reasons for discontinuing PrEP included decreased HIV risk perception, non‐adherence to care plans, insurance barriers, and medication intolerances. Other studies have also found that changes in HIV risk perception and side effects were common reasons for PrEP discontinuation . This heterogeneity in the reasons for discontinuing PrEP suggests that preventing inappropriate discontinuations will likely require diverse or multifaceted interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective chart review at an academic health system in New York found that retention in PrEP care after six months was 42%. In a national study of over 1000 PrEP users at the Veterans Health Administration, 44% of PrEP users discontinued PrEP within the first year , and 38% of PrEP users at a community‐based clinic in San Francisco discontinued PrEP by 13 months . Similarly, 26% of nearly 5000 patients who initiated PrEP between 2012 and 2017 at an integrated healthcare organization in Northern California discontinued PrEP .…”
Section: Discussionmentioning
confidence: 99%
“…To estimate overall—as opposed to direct—covariate effects on each measure of PrEP discontinuation [22], we used directed acyclic graphs to select models including all measured confounders of the relationship of each covariate with PrEP discontinuation, based on the prior PrEP retention literature [1, 3, 9, 23], while excluding any mediators. Confounders included in the model for each covariate are listed in the footnotes of Table 2.…”
Section: Methodsmentioning
confidence: 99%